Prior Coronary Artery Bypass Graft Surgery Impacts 30-day Quality of Life after Percutaneous Coronary Intervention: Evidence from the Victorian Cardiac Outcomes Registry (VCOR): 30-day QoL after PCI in patients with prior CABG - Ho, C.L.B.; Brennan, A.; Dinh, D.T.; Lefkovits, J.; Liew, D.; Si, S.; Reid, Christopher; Norman, Richard (SPRINGER, 2022)
Quality of life following percutaneous coronary intervention (PCI) in patients with coronary artery bypass graft surgery (CABG) has been reported as lower than non-CABG patients, however previous reports pre-date modern developments in PCI and cardiac surgery. This study aimed to examine the 30-day QoL after PCI between patients with and without prior CABG using a contemporary dataset. A retrospective analysis of the Victorian Cardiac Outcomes Registry was undertaken. This study included 36,799 patients who completed the EQ-5D questionnaire that was used to assess the 30-day QoL and was compared between groups with and without prior CABG at baseline. Most of the participants were older than 65 years, more than half were male and had PCI due to acute coronary symptoms (ACS) and nearly 90% of patients received drug eluting stents. Compared to the ‘no prior CABG’ group, the ‘CABG’ group had a significantly higher rate of reporting a health problem (OR 1.30, 95% CI 1.10–1.53), presence of a problem in mobility (OR 1.42, 95% CI 1.15–1.75), personal care (OR 1.49, 95%CI 1.13–1.97) and usual activities (OR 1.39, 95%CI 1.15–1.68), pain/discomfort (OR 1.31, 95%CI 1.11–1.54), and anxiety/depression (OR 1.20, 95%CI 1.02–1.42). Despite modern developments in both PCI and CABG, our study showed a consistent negative association between prior CABG status and 30-day QoL following PCI. There is a need for better targeted cardiac rehabilitation in patients with prior CABG to address their greater relative risk of experiencing poor health.